N-oxygenation of amino compounds: early stages in its application to the biocatalyzed preparation of bioactive compounds - Nóbile, Matías Leonardo (2021)
Among the compounds that contain unusual functional groups, nitro is perhaps one of the most interesting due to the valuable properties it confers on pharmaceuticals and explosives. Traditional chemistry has for many years used environmentally unfriendly strategies; in contrast, the biocatalyzed production of this type of products offers a promising alternative. The small family of enzymes formed by N-oxygenases allows the conversion of an amino group to a nitro through the sequential addition of oxygen. These enzymes also make it possible to obtain other less oxidized N-O functions, such as hydroxylamine or nitroso, present in intermediate or final products. The current substrates on which these enzymes are reported to work encompass a few aromatic molecules and sugars. The unique characteristics of N-oxygenases and the great economic value of the products that they could generate, place them in a position of very high scientific and industrial interest. The most important and best studied N-oxygenases will be presented here.